1998
DOI: 10.1109/48.659450
|View full text |Cite
|
Sign up to set email alerts
|

Teleprogramming for subsea teleoperation using acoustic communication

Abstract: This paper considers the performance of subsea intervention tasks from an unmanned untethered submersible while using acoustic communications. It is argued that the low bandwidth and high delay imposed by acoustic modems makes it unwise to adopt conventional teleoperation techniques and a system is presented which permits subsea teleoperative tasks to be carried out using such limited communication resources. The described implementation employs active techniques to assist the operator both in performing actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Teleprogramming [15][5] extended earlier supervisory control techniques and insulates the operator from the communication delays by automatically issuing a sequence of elementary motion commands, based on the operator's action in the simulated environment, to the remote slave robot. Several free space motions and several contact, sliding and pivoting motions can be generated from parsing the operator's interaction with the simulated environment.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Teleprogramming [15][5] extended earlier supervisory control techniques and insulates the operator from the communication delays by automatically issuing a sequence of elementary motion commands, based on the operator's action in the simulated environment, to the remote slave robot. Several free space motions and several contact, sliding and pivoting motions can be generated from parsing the operator's interaction with the simulated environment.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The human operator gives open-loop commands, possibly with some local closed-loop assistance to avoid disturbances [212]. Often, model-based prediction is used to reduce the effects of the communication delays and give the operator an up-to-date representation of the pose of a manipulator, an example of such a system is described by Sayers [211].…”
Section: Teleoperationmentioning
confidence: 99%
“…These are tasks in which tools are inherently robust to imprecise positioning like the extraction of soil samples on a remote world, or actions which can be performed without physical contact with other objects at all. Stein et al, report a teleprogramming interface was used to attempt to cut tape securing a mock-up of thermal satellite insulation at a remote site [30], and Sayers [28] report an undersea application. In both of these cases, however, numerous manipulation errors occurred during telemanipulation due to discrepancies between the predictive display and actual environment.…”
Section: Introductionmentioning
confidence: 99%
“…One way to enable more natural teleoperation (with or without haptic feedback) under large time delays is modelbased teleoperation, which uses models of the environment acquired from models developed a priori and updated in real time during manipulation [29], [31], [28], [10], [32]. Preliminary work has shown that model-based teleoperation with haptic feedback improves user performance under very simple conditions with delays of up to 4 seconds [23], but manipulation has not yet been accomplished under this paradigm.…”
Section: Introductionmentioning
confidence: 99%